2021
DOI: 10.3389/ftox.2021.643804
|View full text |Cite
|
Sign up to set email alerts
|

Considering Intrauterine Location in a Model of Fetal Growth Restriction After Maternal Titanium Dioxide Nanoparticle Inhalation

Abstract: Fetal growth restriction (FGR) is a condition with several underlying etiologies including gestational disease (e.g., preeclampsia, gestational diabetes) and xenobiotic exposure (e.g., environmental contaminants, pharmaceuticals, recreational drugs). Rodent models allow study of FGR pathogenesis. However, given the multiparous rodent pregnancy, fetal growth variability within uterine horns may arise. To ascertain whether intrauterine position is a determinant of fetal growth, we redesigned fetal weight analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Only one paper used a formula to “normalize” fetal weights (D'Errico et al, 2021). Hereafter “adjusted” will be used in place of “normalized.” To correct for differences in maternal weight and litter size adjusted fetal weight was calculated as follows: Adjusted fetal weightgoodbreak=0.45emFetal weight÷Maternal0.25emnormalGD0.25em200.25embody weightNumber of feti[]sic0.25emin horn. Unusual aspects of their analyses include an adjustment to each individual fetal weight (i.e., not litter means) and use of number of fetuses per uterine horn (and not entire uterus).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one paper used a formula to “normalize” fetal weights (D'Errico et al, 2021). Hereafter “adjusted” will be used in place of “normalized.” To correct for differences in maternal weight and litter size adjusted fetal weight was calculated as follows: Adjusted fetal weightgoodbreak=0.45emFetal weight÷Maternal0.25emnormalGD0.25em200.25embody weightNumber of feti[]sic0.25emin horn. Unusual aspects of their analyses include an adjustment to each individual fetal weight (i.e., not litter means) and use of number of fetuses per uterine horn (and not entire uterus).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we searched the National Toxicology Program (NTP) database and found five unpublished EFDT and four range‐finding rat studies that also reported adjusted fetal weights. The four publications reporting adjusted or normalized fetal weight (Catlin et al, 2018a; D'Errico et al, 2021; Lee et al, 2022; Sorell & Graziano, 1990) used different adjustment methods, which were either statistically based or formula‐based. Catlin et al (2018a) is one of the five aforementioned EFDT studies conducted by the NTP that display adjusted fetal weight; however, it is the only one published in the open literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… D’Errico et al (2021) used a novel method to adjust fetal weights to account for the uterine horn side and the number of fetuses per horn, according to the following formula: …”
Section: Comments On the Normalized Fetal Weight Formulamentioning
confidence: 99%
“…We have read with interest the paper by D’Errico et al (2021) and question the authors’ suggestion that fetal weights should be normalized based on their location within the uterus. Fetal weight effects are considered the most sensitive endpoint of embryo–fetal developmental toxicity (EFDT) studies ( USEPA, 1991 ).…”
Section: Introductionmentioning
confidence: 99%